Hybrid CNN-Transformer Architecture for Robust Liver Tumor Segmentation in 2D CT Slices - Huda Dham Bader; Mohammed Sabah Jarjees (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2026)
Liver tumor segmentation from CT scans is a task affected by class imbalance, low contrast, and small lesion size. Manual segmentation is time-consuming and also suffers from inter-observer variability. We propose a 2D CNN-Transformer model with 20.3M parameters in an encoder–decoder structure with four transformer layers (8 heads, 2048 feedforward dimension). The model processes 2D axial slices due to GPU memory limits. The loss function combines Cross-Entropy, Dice, and Focal losses with α = 0.25 and γ = 2.0. Preprocessing includes CLAHE (clip limit = 2.0, 8×8 tiles) and gamma correction (γ = 1.2). From the LiTS dataset (131 volumes), 11 volumes with 1,688 slices were selected based on tumor presence, annotation quality, and artifact removal. A patient-level split of 80% for training, 10% for validation, and 10% for testing was used to prevent data leakage. The model achieved liver Dice = 0.916 ± 0.122 and tumor Dice = 0.810 ± 0.304. The 95% confidence intervals using bootstrapping (1,000 resamples) were [0.897–0.934] for liver and [0.765–0.856] for tumor. Best validation results at Epoch 98 were liver Dice = 0.938, tumor Dice = 0.823, and accuracy = 0.992. Pixel accuracy was 99.20% and was not used as the main metric due to class imbalance, where background pixels exceed 90%. An ablation study showed that CLAHE and gamma correction improved tumor Dice by 8.6% and liver Dice by 3.3% compared to a baseline without preprocessing. The model shows performance for liver tumor segmentation on a LiTS subset. External validation on the full dataset and multi-center data is required before clinical use